Perfection of management principles by the safety signals of medicinal products - B. K. Romanov; V. K. Lepakhin; E. O. Zhuravleva; A. V. Astakhova; S. V. Glagolev; V. A. Polivanov (Безопасность и риск фармакотерапии)
Systematic evaluation of management principles by signals on medicinal drugs safety is submitted. The sources of signals, the approaches to the detection signal processing and detection, validation, analysis and prioritization, signal assessment are considered. A review of the individual security reports is demonstrated. A statistical analysis of large databases and processes of their regulation was shown. Practical recommendations for the identification of signals in national and international databases are given.